2002
DOI: 10.1038/sj.bjc.6600499
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of cytochrome P4501A1 and oesophageal squamous-cell carcinoma in Taiwan

Abstract: Several in vitro studies have demonstrated that genetic polymorphisms result in functionally significant changes in cytochrome p4501A1 (either CYP1A1 MspI or exon 7) but the few epidemiologic studies of these polymorphisms in oesophageal squamous-cell carcinoma have been inconclusive. These inconclusive results motivated us to further examine the relationship between CYP1A1 MspI and exon 7 polymorphisms and risk of oesophageal cancer. In total, 146 cases of oesophageal squamous-cell-carcinoma and 324 control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…But associations were null after adjusting for age, gender, smoking, drinking and family history of cancer. This result is consistent with the study of Wu et al (2002). Guo et al (2005) found that individuals with the MspI T/C or C/C genotype had a higher risk of developing esophageal cancer than those with the T/T genotype (OR:1.93,95%CI:1.01-3.84).…”
Section: Discussionsupporting
confidence: 82%
“…But associations were null after adjusting for age, gender, smoking, drinking and family history of cancer. This result is consistent with the study of Wu et al (2002). Guo et al (2005) found that individuals with the MspI T/C or C/C genotype had a higher risk of developing esophageal cancer than those with the T/T genotype (OR:1.93,95%CI:1.01-3.84).…”
Section: Discussionsupporting
confidence: 82%
“…Conflicting results have been published regarding the association of CYP1A1 polymorphisms with risk of esophageal cancer in Asians and Caucasians [85][86][87][88][89][90]. In one study, CYP1A1 MspI T/C polymorphism was not associated with esophageal cancer [91].…”
Section: Esophageal Cancermentioning
confidence: 91%
“…Two genetic polymorphisms of the CYP1A1 gene have been reported to be associated with differences in the activity of the AHH enzyme activity -an isoleucine to valine substitution in exon 7 (m2 polymorphism) and a thymine/cytosine point mutation in the MspI restriction site (m1 polymorphism; Autrup 2000). Cytochrome P4501A1 (CYP1A1) m1 and m2 gene variants have been shown to be in close linkage disequilibrium and to be associated with a more inducible form of CYP1A1 (Wu et al 2002). The ensuing higher levels of the corresponding enzymes would result in an increased capacity to activate polycyclic aromatic hydrocarbons, producing highly reactive electrophilic intermediates that might damage DNA (Kawajiri et al 1990).…”
Section: Introductionmentioning
confidence: 99%